1990
DOI: 10.1073/pnas.87.24.9717
|View full text |Cite
|
Sign up to set email alerts
|

Activation of early events of the mitogenic response by a P2Y purinoceptor with covalently bound 3'-O-(4-benzoyl)-benzoyladenosine 5'-triphosphate.

Abstract: 3'-O-(4-Benzoyl)benzoyl-ATP (BzATP), a photoaffinity analog of ATP, was used as a ligand for a P2Y purinoceptor (adenine nucleotide receptor) present in intact Swiss 3T3 and 3T6 cells and A-431 epidermoid carcinoma cells. Photolysis of serum-starved cells in the presence of 10-50 microM BzATP, followed by extensive washing to remove unincorporated BzATP, induced the release of arachidonic acid. A trace (less than 0.01%) of photoincorporated BzATP was as effective as when 50 microM BzATP or ATP was contained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…For example, a role for ATP has been claimed in embryonic cell migration and during morphogenesis [Lohmann et al, 1991;Kubo, 1991;Rathbone et al, 1992al. Extracellular ATP has also been implicated as a mediator of programmed cell death or apoptosis [Di Virgilio et al, 1990;Zheng et al, 1991;Murgia et al, 19921; purine agonists have been shown to be involved in the trophic effects of sympathetic innervation [Albino-Teixeira et al, 19901; ATP has been implicated as a fusion signal for developing skeletal muscle cells [Keresztes et al, 19911; and purines can act synergistically with growth factors to influence growth mitogenesis and morphogenesis [Huang et al, 1989;Gonzalez et al, 1990;Rathbone et al, 1992bI. It has been suggested that extracellular ATP and ADP may play a physiological role in wound healing and as a mitogenic agent in the nervous system [Wang et al, 19901.…”
Section: Long-term "Trophic" Actions Of Purinesmentioning
confidence: 99%
“…For example, a role for ATP has been claimed in embryonic cell migration and during morphogenesis [Lohmann et al, 1991;Kubo, 1991;Rathbone et al, 1992al. Extracellular ATP has also been implicated as a mediator of programmed cell death or apoptosis [Di Virgilio et al, 1990;Zheng et al, 1991;Murgia et al, 19921; purine agonists have been shown to be involved in the trophic effects of sympathetic innervation [Albino-Teixeira et al, 19901; ATP has been implicated as a fusion signal for developing skeletal muscle cells [Keresztes et al, 19911; and purines can act synergistically with growth factors to influence growth mitogenesis and morphogenesis [Huang et al, 1989;Gonzalez et al, 1990;Rathbone et al, 1992bI. It has been suggested that extracellular ATP and ADP may play a physiological role in wound healing and as a mitogenic agent in the nervous system [Wang et al, 19901.…”
Section: Long-term "Trophic" Actions Of Purinesmentioning
confidence: 99%
“…In particular, (i) BPs can be activated at wavelengths (> 320 nm) that are not associated with protein damage, (ii) BPs are reported to give highly efficient covalent labeling via insertion into unreactive C-H bonds, (iii) BP photolabeling shows no interference from water or bulk nucleophiles, and (iv) no special lighting conditions are necessary during synthesis and biochemical manipulations. Recently, the BP moiety has been used in polypeptides as 4-benzoylphenylalanine (ONeil & DeGrado, 1989;ONeil et al, 1989;Boyd et al, 1991;McNicoll et al, 1992;Shoelson et al, 1993;Williams & Shoelson, 1993) and as 4-benzoylbenzoyl esters and amides in nucleotides (Mahmood et al, 1989;Boyer et al, 1990;Chavan et al, 1990;Gonzalez et al, 1990;Pal & Coleman, 1990;Aloise et al, 1991;Bar-Zvi et al, 1992;Pal et al, 1992;Rajagopalan et al, 1993;Salvucci et al, 1993;Zarka & Shoshan-Barmatz, 19931, in sugars (Holman et al, 1988), in phospholipids (Ishidate et al, 1992), and in proteins (Leszyk et al, 1988;Agarwal et al, 1991;Rajasekharan et al, 1991;Combeau et al, 1992;Thiele & Fahrenholz, 1993). Interactions within lipid bilayers have also been probed using BP-lipid analogs (Yamamoto et al, 1993).…”
Section: Introductionmentioning
confidence: 97%
“…The production of PGE, and the accumulation of cyclic AMP were also stimulated, in a pertussis toxin sensitive manner (Gonzalez et al, 1990). Thus, a trace amount of BzATP, covalently linked to a Pzy purinoceptor, activated three "early events" as effectively as 50 pM ATP under ordinary conditions.…”
Section: Resultsmentioning
confidence: 97%
“…We previously observed that photolysis of quiescent 3T3 or 3T6 cells in the presence of BzATP, a photoaffinity analogue of ATP, followed by extensive washing to remove unincorporated BzATP, induced the release of arachidonic acid. The production of PGE, and the accumulation of cyclic AMP were also stimulated, in a pertussis toxin sensitive manner (Gonzalez et al, 1990). Thus, a trace amount of BzATP, covalently linked to a Pzy purinoceptor, activated three "early events" as effectively as 50 pM ATP under ordinary conditions.…”
Section: Nucleotide Specificity For Stimulation Of Dna Synthesis and mentioning
confidence: 93%
See 1 more Smart Citation